Precautionary and Liquidity Line : Operational Guidance Note. (Policy Papers; Policy Paper ;, 2018)
This note provides general guidance on the use of the Precautionary and Liquidity Line (PLL). After an overview of the instrument, explaining its specific nature, the operational issues are grouped into five areas: -- an outline of the process and specific steps that need to be followed if a member expresses interest in an arrangement; -- guidance on access, phasing, and purchases; -- guidance on determining qualification of a member and appropriate ex-post conditionality; and -- a guide to the semi-annual review process. The note is an aid to the implementation of the policy and its underlying principles. If there is any instance in which a provision of the guidance note or its implementation conflicts with Board policy, Board policy prevails. It will be revised as needed, for example following relevant policy reviews.